Street pattern effects on snatch incidents / Anith Nabilah Mustafa and Siti Rasidah Md Sakip - Anith Nabilah, Mustafa; Siti Rasidah, Md Sakip (UiTM Press Universiti Teknologi MARA, Perak, 2017)
Snatch theft has become a serious issue in Malaysia especially in cities. It tends to happen in cities because there is a possibility to commit it and both crime and urban are often associated with each other. The aim of this paper is to identify the street pattern in urban area that influence the snatch theft activities. The street pattern is identified by using the Geographic Information System (GIS) to determine and analyse the area with high snatch theft cases. It was found that the area with high number ofreported snatch theft cases possessed a fragmented parallel street pattern.